Utilization of Public Relations Program in Educating the Millennials About Papua-Indonesia Separatism Issue - Dewi Febrina Iriani; Gaby Mariska Runtu; Santo Medy Wibisono; Bambang Sumaryanto (COMMENTATE: Journal of Communication Management, 2021)
The issue of Papuan-Indonesian separatism is not new in Indonesia, and this has become the Ministry of Foreign Affairs' concentration to deal with. In this case the project planners  believe that there is a humanitarian and dignified perspective that needs to be improved by the government. Therefore, the measure needs a Public Relations approach as an effort to support government programs in overcoming the issue of Papua-Indonesia separatism. The method employed in this research is to use strategic planning public relations by Ronald Smith, which consists of 9 steps in 4 phases. The concepts used in this project are Public Relations, Online PR, Social Media, and Event Design. By approaching PR through social media programs and events, the project planners claimed to be able to approach millennials to shape their awareness of Papua, so they have a good image of Papua. This will have an impact on the spread of positive Papuan issues on social media, which was dominated with negative issues regarding separatism. The success of the program will be evaluated by the number of participants involved in the event, social media followers, and positive news spread on social media.